L'Allusion et l'Accès - Peter Vernon, Claudine Raynaud (dir.) (Presses universitaires François-Rabelais, 2005)
L'Allusion et L'Accès follows on from work previously published in GRAAT, in particular Usure et Rupture - Breaking Points (GRAAT 13) and Fonctions du Cliché - Du Banal à la Violence (GRAAT 16). The present conference aimed to articulate the strategies that the literary text deploys to access the unsayable, whilst, simultaneously, keeping in mind the notion of play contained in the etymology of allusion: alludere. Allusion and Access, then, are two vast subjects put into juxtaposition and pe...